Enhanced effect of pyrite on the removal of metronidazole by zero valent iron - Linting, Han; Kun, Chen; Huaping, Dong; Jianfa, Li; Yimin, Li (Journal of colloid and interface science, 2021)
[Display omitted] The abuse and improper disposal of antibiotics including metronidazole (MNZ) result in serious contamination in aquatic environments. In this study, pyrite, which was not reactive for MNZ removal, was simply mixed with zero valent iron (ZVI) to efficiently remove MNZ in anaerobic aqueous solutions. A dual ZVI/pyrite system consisting of ZVI (1.0 g/L) and pyrite (4.0 g/L) removed MNZ completely in 360 min within a broad pH0 range (5.0–9.0), and it still maintained a high removal efficiency (~80%) even at a high pH0 of 10.0. By contrast, single ZVI (1.0 g/L) showed much lower efficiency (4.8%–22.0%) within the same pH0 range (5.0–10.0). On investigating the mechanism of MNZ removal, the cooperation between ZVI and pyrite enhanced the surface corrosion of ZVI and facilitated the redox cycle of Fe(III)/Fe(II) to generate more sorbed Fe(II), which was a dominant reactive species for MNZ removal. Pyrite also activated the ZVI surface to form FeS@Fe in situ, accelerating the electron transfer from Fe0 core to the surface-enriched MNZ, and stimulated the formation of green rust sulfate on the ZVI surface to further promote MNZ removal. LC-MS analysis confirmed ZVI/pyrite reductively transformed MNZ into readily biodegradable products by denitration and cleavage of hydroxyethyl.